2016
DOI: 10.1063/1.4949561
|View full text |Cite
|
Sign up to set email alerts
|

Phonon thermal conductivity of monolayer MoS2

Abstract: We use nonequilibrium molecular dynamics modeling using Stillinger–Weber interatomic potential to investigate the thermal properties of monolayer molybdenum disulfide (MoS2) nanoribbons. We study the impact of factors such as length, edge chirality, monovacancies, and uniaxial stretching on the thermal conductivity of MoS2 nanoribbons. Our results show that longer ribbons have a higher thermal conductivity, and the thermal conductivity of infinitely long zigzag and armchair MoS2 nanoribbons is, respectively, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The phonon dispersions were the first features to be studied from a theoretical viewpoint [13,14,15] and the Raman active modes were also experimentally reported [15]. Further theoretical calculations have been able to determine the thermal conductivity from molecular dynamics [16,17,18] and from lattice dynamics using density functional theory (DFT) through the Boltzmann transport equation (BTE) under the relaxation time approximation (RTA) [19]. Recently, more accurate solutions of the BTE [20] have allowed to compute with greater accuracy the thermal conductivity of MoS 2 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The phonon dispersions were the first features to be studied from a theoretical viewpoint [13,14,15] and the Raman active modes were also experimentally reported [15]. Further theoretical calculations have been able to determine the thermal conductivity from molecular dynamics [16,17,18] and from lattice dynamics using density functional theory (DFT) through the Boltzmann transport equation (BTE) under the relaxation time approximation (RTA) [19]. Recently, more accurate solutions of the BTE [20] have allowed to compute with greater accuracy the thermal conductivity of MoS 2 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Small κ could jeopardize heat dissipation of TMD-based electronics, and techniques to enhance the cross-plane thermal conductivity are required. Previous theoretical studies of strain's effect on thermal conductivity in TMDs have reached inconsistent conclusions [38][39][40][41][42], and experimental studies have not yet been reported. Thus, exploring the tunability of thermal conductivity in TMDs with strain will not only have scientific significance, but also inform thermal management techniques in all TMD-based electronic devices.…”
mentioning
confidence: 96%
“…In this sense, the existence of the additional phonon at the 50 ps (0.02 THz) oscillation period (Figure e) is attributed to the difference in heat conduction (≈20% in monolayer MoS 2 ) . Further, factors that determine phonon transport in rigid crystalline structures include the vacancy states, elastic states, and the lattice chirality . Thus, for the highly confined van der Waals structure of 2D semiconducting materials with limited influence from defect generation in the stress‐free state, the difference in the lattice chirality should be the major mechanism of acoustic phonon generation .…”
mentioning
confidence: 99%
“…Our image‐based TSHG measurement approach, which features superior spatial resolution and lattice orientation‐selectivity, makes it possible to directly compare the difference between ultrafast quasiparticle dynamics generated not only from the layer thickness but also the chirality, which is occasionally observed during the fabrication of 2D materials. The edge chirality of 2D materials plays a critical role in determining various material characteristics, such as lattice vibration, conductivity, and carrier transport . Theoretically, the armchair edge of MoS 2 is known to experience a drastic bandgap shift between semiconducting and metallic properties in the presence of an electric field, while the carrier transport is more efficiently passivated at zigzag (ZZ) edges .…”
mentioning
confidence: 99%
See 1 more Smart Citation